Assessing the quality of footwear marks recovered from simulated graves - Stephens, Madeleine; Errickson, David; Giles, Stephanie B.; Ringrose, Trevor J. (Elsevier, 2020)
Footwear marks are one of the most frequently encountered evidence types recovered from a crime scene and can provide valuable scene intelligence regarding potential suspects. It has been acknowledged that impressions of footwear and tools can be recovered from graves, but previous studies have only focused on tool mark recovery. This has led to a lack of published information regarding footwear mark recovery from graves. It is therefore important to demonstrate whether the recovery of footwear marks is feasible and, if so, under what conditions this can be achieved. To address recovery, this study, placed 60 three dimensional (3D) impressions of footwear marks within 60 simulated graves. This was done to assess time (1, 2, 4 months) and at known depths (20, 30, 40 cm). The footwear marks within the graves were covered with clothing or left uncovered. The shoe’s design patterns were grouped and counted in a photographic comparison between the 3D footwear impressions, placed within the test-pits, and any recovered impressions. A grading system was adapted by the authors to score the quality of footwear impressions observed during recovery. The results demonstrate that the preservation and recovery of footwear impressions from graves is feasible. The simulated graves covered with clothing showed better preservation of footwear impressions, but there was no clear evidence that time or depth had an effect. The authors note that careful consideration and vigilant excavation skills are needed when excavating graves which may bear potential footwear marks, as their recovery will lead to an increased amount of intelligence that can link suspects to homicide scenes.
Keywords: Excavation; Footwear impression; Forensic archaeology; Trace evidence